́Sr̄i Gajendra Sịmha Solȧnk̄i - Solȧnk̄i, Gajendra Sịmha, 1923- (R̄ajasth̄ana s̄ahityak̄ara prastuti, 2007)
Selected works of Gajendra Simha Solanki, b. 1923, Hindi author from Rajasthan; includes study of his works also.